Management of metabolic resources for a 20-km cycling time-trial using different types of pacing - Chuckravanen, D.; Rajbhandari, S. (Journal of Human Sport & Exercise, 2015)
Pacing is crucial for improving human performance in time-trial physical exercise. This study examined the effect of different types of pacing (self pace, variable pace and even pace) on the energy expended from the aerobic system and anaerobic system for a 20-km time-trial cycling exercise. In addition, the degree of homeostatic disturbance caused by each type of pacing was analysed to find out the effect of pacing on the human body. Furthermore, the relationship between the Ratings of Perceived Exertion (RPE) and blood lactate concentration was investigated, and associated to these types of pacing. Here, in this study, we showed that even pace was aerobic energy system dependent, and variable pace was anaerobic energy system dependent. Also, the Hazard Score index demonstrated that the variable pace time-trial caused the greatest homeostatic disturbance and there was a positive relationship between RPE and blood lactate concentration.